Minimal tillage and intermittent flooding, rice irrigation strategies to reduce the production of mosquitoes that transmit malaria - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Preliminary small-scale trial to demonstrate that minimal tillage and intermittent flooding are effective in reducing the production of malarian vector mosquitos was completed and published. Practices, tested in the dryland rice fields of Malanville (Benin), significantly reduced anopheles breeding sites and larval densities.